2007
DOI: 10.1080/02652030701422465
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-alkenals in polyunsaturated fatty acids-fortified infant formulas and other commercial food products

Abstract: 4-Hydroxy-2-hexenal (HHE) and 4-hydroxy-2-nonenal (HNE) were determined using selected ion-monitoring gas chromatography-mass spectrometry (GC-MS) in 56 kinds of commercially available PUFA-fortified foods including infant formulas and baby foods. HHE and HNE, each specifically coming from the oxidation of n-3 and n-6 polyunsaturated fatty acids (PUFA), were observed at <10-77 and 41-132 microg kg(-1) in the infant formulas (n = 12) and at <10-52 and 36-116 microg kg(-1) in the baby foods (n = 7), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
(25 reference statements)
3
18
0
1
Order By: Relevance
“…In our study, the quantity of ingested 4-HHE per day as the one measured in lipid mixtures of high-fat diets was in the range 1-8 nmol/ day. This is slightly lower than in Surh et al study ( 25 ); nevertheless, our experimental conditions were relevant considering realistic food intakes.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In our study, the quantity of ingested 4-HHE per day as the one measured in lipid mixtures of high-fat diets was in the range 1-8 nmol/ day. This is slightly lower than in Surh et al study ( 25 ); nevertheless, our experimental conditions were relevant considering realistic food intakes.…”
Section: Discussionmentioning
confidence: 46%
“…Surh et al reported that the Korean daily exposure to 4-hydroxy-2-alkenals was 14 nmol/day for 4-HHE and 17 nmol/day for 4-HNE ( 25 ). In our study, the quantity of ingested 4-HHE per day as the one measured in lipid mixtures of high-fat diets was in the range 1-8 nmol/ day.…”
Section: Discussionmentioning
confidence: 57%
“…Diet may influence tissue levels of HNE, which derives from arachidonic and linoleic x6-acids, are often abundant especially in Western diets (246). However, HNE levels can be also affected by antioxidant intake, as well as by intestinal microbiota.…”
Section: The Role Of Lipid Oxidation End-products In Ibdmentioning
confidence: 99%
“…Las fórmulas lácteas han ido incorporando, en la medida que es tecnológicamente posible, los componentes fundamentales de la leche materna y aunque aún su composición dista mucho para igualarse a la secreción láctea, en los últimos años se han logrado progresos muy importantes (Carver, 2003;Valenzuela y Nieto, 2003;Prosser et al, 2010;Martinez y Ballew, 2011). En lo que respecta al tipo de ácidos grasos que aportan estas fórmulas, es necesario identificar aquellas que contienen LA y ALA y aquellas que además contienen AA y DHA, ya que la tendencia actual es adicionar los alimentos infantiles con estos ácidos grasos; y el problema surge cuando el lactante debe alimentarse con fórmulas convencionales, generalmente ricas en ácido linoleico, en algunos casos con aportes suficientes de ácido α-linolénico, pero pobres en ácido docosahexaenoico y araquidónico (Morales, 1994;Surh et al, 2007;Rosenfeld et al, 2009;Prosser et al, 2010;Makrides et al, 2011;Martinez y Ballew, 2011).…”
Section: El Papel De Los Lc-pufa En El Desarrollo Visual Y Cerebralunclassified